Behavior of Plastic Working in Oil-Field Equipment (International Journal of Innovative Research in Computer Science & Technology, 2017)
Researches were made for the purpose of  increase of labor productivity and replace of non ferrous metals and ferrous metals by plastics. Details  for this purpose are selected with a certain  characteristic that further the developed  technological process could be applied in the oil and  gas industry.Plastic materials have the difficult  intense nature and differ from metals markedly the  expressed deviations from property of ideally elastic  solid bodies.
Keywords: Plastic materials; reliability; quality; durability; thermalendurance